2012
DOI: 10.1086/667369
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Central Line–Associated Bloodstream Infections in Hemodialysis Patients

Abstract: An increasing proportion of central line-associated bloodstream infections (CLABSIs) are seen in outpatient settings. Many of such infections are due to hemodialysis catheters (HD-CLABSIs). Such infections are associated with substantial morbidity, mortality, and excess healthcare costs. Patients who receive dialysis through a catheter are 2-3 times more likely to be hospitalized for infection and to die of septic complications than dialysis patients with grafts or fistulas. Prevention measures include minimiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
18
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 57 publications
0
18
0
1
Order By: Relevance
“…In addition to the significant patient morbidity associated with these infections, direct medical costs are approximately $20,000 per occurrence (2,3). As such, prevention of CLABSI has been declared a United States health care priority (4).…”
mentioning
confidence: 99%
“…In addition to the significant patient morbidity associated with these infections, direct medical costs are approximately $20,000 per occurrence (2,3). As such, prevention of CLABSI has been declared a United States health care priority (4).…”
mentioning
confidence: 99%
“…Boyce recently reviewed all antimicrobial lock studies (antibiotic-and non-antibiotic-based) performed from 1999 to 2012 and concluded that antimicrobial locks should be used for CRBSI prevention in all hemodialysis units (11). In addition, five meta-analyses or systematic reviews (12)(13)(14)(15)(16) published during this time period indicate significant reductions in CRBSI; in particular, two meta-analyses reported a number needed to treat to prevent one CRBSI of 3 to 4 (12,13).…”
mentioning
confidence: 99%
“…Some CVCs specify in their package insert instructions for use that the polymers used are broken down by some ointments or solutions and should not be used. Antibiotic and nonantibiotic antimicrobial lock solutions have proven effective in reducing infections (54)(55)(56)(57). A standard approach to catheter care, defined by facility policy and verified by practice audits, will likely result in fewer CVC-associated bloodstream infections.…”
Section: Central Venous Catheters (Cvcs)mentioning
confidence: 99%